Tension Test for Axially Vibrated Prestressing Fine-Rolled Screw-Threaded Steel Bars Based on Thread-Contact Connection - Xingu Zhong; Tianyu Zhang; Chao Zhao; Xiaojuan Shu; Mingyan Shen; Yohchia Frank Chen (Advances in Civil Engineering)
The interface between anchor plate and anchorage nut can be considered as a coupling spring whose stiffness is essentially the contact stiffness related to normal force at the contact surface, thus removing the usual assumption of fixed connection. The nut threads and steel bar are also connected with a coupling spring with the stiffness determined based on the threads treated as cantilever components. An analytical model was developed to assess the axial vibration of an anchorage system consisting of prestressing fine-rolled screw-threaded steel bars (P/S FSSBs). Both laboratory model and field tests show that the contact stiffness between anchor plate and anchorage nut has good a linear relationship with the effective tension of prestressed tendons. The vibration model was used to obtain the natural frequency and tensile force of a P/S FSSB. It is shown to be feasible and practical. According to the analytical model and test method presented in this paper, the proposed tension tester for P/S FSSBs possesses the features of repeated use, rapid testing, and minimized impact on the construction and is thus suggested for wider practical applications.